Light-Based External Human Machine Interface: Color Evaluation for Self-Driving Vehicle and Pedestrian Interaction. (November 2019) - Faas, Stefanie M.; Baumann, Martin
In today's road traffic pedestrians seek eye contact with drivers to move along safely. Such communication is no longer possible with self-driving vehicles. Previous research shows that an external Human-Machine-Interface (eHMI) provides an interface between self-driving vehicles and pedestrians. However, recommendations for standardization are still being developed. The study compares the colors white and turquoise for eHMI lamps indicating that the automated driving system is engaged. The colors are evaluated in a street-crossing scenario and a parking lot scenario with a Wizard-of-Oz vehicle equipped with eHMI lamps mounted on top of the vehicle. We conducted questionnaires and structured interviews with N =59 participants to identify eHMI design guidelines. Our research provides evidence that turquoise facilitates pedestrians' factors like visibility, discriminability, sense of safety and trust higher than white. The results are consistent among traffic scenarios. This paper contributes in formulating research-based design guidelines to improve pedestrian safety.